Insulinotropic Activity of Methanolic Extract of Mesua ferrea Linn. - Umamahesh Balekari; Ciddi Veeresham (Journal of Basic & Applied Sciences, 2015)
Mesua ferrea flowers have been used in the Indian traditional medicine for treating various diseases. In present study, the Mesua ferrea flowers methanolic extract (MFME, 200 mg/kg bw) was studied for anti diabetic activity and underlying mechanisms for its activity. In Streptozotocin induced diabetes rats model, MFME treatment enhanced plasma insulin levels by 69.53% (P<0.0001) than the diabetic control rats. In diabetic rats, MFME treatment significantly restored body weight and blood glucose levels to normal. In Insulin release studies on MIN6 beta cells, insulin release was potentiated in a dose dependent manner of extract and glucose. The insulin stimulatory effect of MFME was stimulated by 3-isobutyl-1-methyl xanthine, Glibenclamide and elevated extracellular calcium. In distinction, the stimulatory effect was inhibited with diazoxide, nifedipine, EGTA and K+ depolarized media. These results indicate MFME anti diabetic activity might be a result of insulin secretagogue effect through beta cell physiological pathways.